Self Esteem and its Associated Factors in Patients with Multiple Sclerosis - Sharifi Neyestanak ND; Ghodoosi Boroojeni M; Seyedfatemi N; Heydari M; Hoseini AF (Iran University of Medical Sciences, 2012)
Background & Aim: Multiple Sclerosis (MS) as a progressive disorder can deteriorate body image and the feeling of attractiveness and influence patients' self-esteem through changing their cognitive experiences and attitude towards their body. Accordingly this study was conducted with aim of assessing self esteem and its related factors in patients with MS.   Material & Methods: It was a descriptive, cross-sectional study. The subjects (n= 395) were recruited by convenience sampling from Multiple Sclerosis Society in Tehran. Rosenberg Self-Esteem Inventory was used as data collection tool. Data was analyzed by independent t-test, ANOVA, Pearson correlation, Spearman correlation coefficient, chi-square test and post hoc Scheffe test using SPSS-PC (version 16).   Results: The mean score of self-esteem was 17/5 ± 53/20. Most patients had moderate self-esteem, and only a small percentage of them (16.2%) had high self esteem. There were significant relationship between the patients' self-esteem and their age, educational level, marital status, employment status and the duration of disease (P<0.05) .   Conclusions: Nurses are able to consider the patients' esteem needs by recognition of high risk groups and provide appropriate interventions to improve the quality of life of these patients and their families.  Received: 3 Sep 2012   Accepted: 10 Nov 2012